Mediterrane dorpsculturen - Gailly, Arthur; Hermans, P.; Leman, J. (Brussel: Cultuur en Migratie, 1983)
"A. Gailly, P. Hermans & J. Leman Herwerkte uitgave van : Kultuurleven (1980) 47, p. 820-840 + p. 928-935"